Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan di Hotel PRL - Ni Made Ari Kusuma Dewi; Ni Luh Gde Sri Sadjuni; Ni Desak Made Santi Diwyarthi (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
A positive work environment, characterized by fair leadership and supportive colleagues, can enhance employee comfort and performance. Conversely, a negative work environment can hinder performance. This study aimed to examine the influence of the work environment on employee performance at Hotel PRL. The study population comprised 582 employees at the supervisor and staff levels, with a sample of 85 respondents selected through probability sampling using proportionate stratified random sampling. Data were collected through a questionnaire with a 5-point Likert scale to measure 24 statement items. Data analysis techniques employed included simple linear analysis, t-test, and the coefficient of determination, processed using SPSS version 29. The results showed that the work environment had a positive and significant effect of 79.8% on employee performance. This highlights the importance of creating a conducive work environment to improve employee performance, especially since the average employee performance scores in 2022 and 2023 were still below the established standards, despite the positive influence of the work environment..